Mapping World Trends in the Peatland Restoration Literature: An Overview of Bibliometric Analysis - Pratama, Irfandi; Waworundeng, Welly; Sampe, Stefanus; Rahmat, Al Fauzi; A’yun, Lulu Qurrat (Indonesian Journal of Environmental Management and Sustainability, 2025)
Anthropogenic activities have degraded peatlands in various regions worldwide. To protect and restore peatlands and their ecosystems, sustainable peatland restoration efforts have been undertaken. These efforts have attracted the attention of researchers to assess the success rate, benefits, and protection of restored ecosystems. This study highlights trends, issues, and recent developments through a bibliometric analysis of articles on peatland restoration from an environmental security perspective, published in the Scopus database. The researcher identified 94 journal articles published between 1994 and 2022 and analyzed them using VOSviewer and NVivo 12 Plus software. The results show that research on peatland restoration is playing an important role from an environmental security perspective with increasing recent progress, and has high relevance for rewetting, revegetation, and cost benefits. In contrast, the main issues in peatland restoration are water, ecosystem, and carbon. Experts measure restoration progress through water levels and related issues. Then the peatland ecosystem absorbs about 30% of the world’s carbon and vice versa; when degraded, they release carbon. Recommendations for future research focus on harmonizing peatland restoration efforts with an environmental security perspective and educating local communities about the benefits that can increase the success of restoration and preservation of peatland ecosystems, as well as efforts to increase protection through advocacy for these marginal ecosystems.